2013
DOI: 10.3724/sp.j.1005.2013.00017
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatics advances in protein ubiquitination

Abstract: Ubiquitin-proteasome system (UPS) mediates 80% to 85% of the protein degradation in eukaryotic cells. The characteristics of UPS pathway are dependent on ATP, efficient and highly selective. Ubiquitination not only participates in protein degradation, but also directly affects protein activity and localization. Ubiquitination can regulate multiple cellular processes including cell cycle progression, apoptosis, transcriptional regulation, DNA damage repair and immune response. More and more datasets about UPS a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…They were then identified through analysis of their morphological characteristics under a microscope to confirm that they were all Ae. aegypti 33 . The first generation of artificially reared female adults (F1) was bioassayed for resistance and compared with pyrethroid‐sensitive adult Ae.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…They were then identified through analysis of their morphological characteristics under a microscope to confirm that they were all Ae. aegypti 33 . The first generation of artificially reared female adults (F1) was bioassayed for resistance and compared with pyrethroid‐sensitive adult Ae.…”
Section: Methodsmentioning
confidence: 99%
“…aegypti. 33 The first generation of artificially reared female adults (F1) was bioassayed for resistance and compared with pyrethroid-sensitive adult Ae. aegypti from Hainan Province, China, which have been raised in the laboratory for more than 10 years and have never been exposed to insecticides.…”
Section: Mosquito Samplingmentioning
confidence: 99%
“…Research has shown that the UPS is crucial for protein degradation in cells and that it can destroy up to 80%–85% of proteins in eukaryotic cells ( Amm et al, 2014 ). When a ubiquitin tag is added to a substrate, it can alter the substrate’s function, localization, protein interaction, or stability and then regulate many different cellular life activities ( Lu et al, 2013 ; Streich Jr and Lima, 2014 ). These activities are crucial to cell growth.…”
Section: The Ubiquitin-proteasome System (Ups) Pathwaymentioning
confidence: 99%
“…The ubiquitin proteasome pathway (UPP), a major intracellular system for ATP-dependent extra-lysosomal protein degradation in the cell cycle, mediates the degradation of 80–85% of intracellular proteins. It consists of ubiquitin, ubiquitin-activating enzymes E1, ubiquitin-conjugating enzymes E2, ubiquitin ligases E3, proteasome and deubiquitinating enzyme [ 16 ]. Numerous studies have demonstrated that UPP plays critical roles in controlling the levels of various cellular proteins, thereby regulating basic cellular processes such as cell division and growth, apoptosis, signal transduction, DNA damage and repair, immune response, and so on [ 17 , 18 , 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%